2015
DOI: 10.18203/2320-1770.ijrcog20151273
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thyroid hormone status in pre-eclampsia: a tertiary care hospital based study

Abstract: Background: The objective of the study was to study the association between thyroid hormone status with preeclampsia and correlate it with severity of pre-eclampsia. Methods: In this case control study, 200 women attending tertiary care hospital between the study period September 2012 to August 2014 were recruited in the study in which 100 women were cases (diagnosed as preeclampsia) and 100 were taken as control (healthy normotensive women). Assessment of thyroid status of cases and control was done. Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(4 reference statements)
2
2
1
Order By: Relevance
“…Age, parity and BMI were comparable in both groups of women. Similar observations were reported by others [2,8] . Casey et al [10] observed hypothyroid women to be older and U Nayki et al [14] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Age, parity and BMI were comparable in both groups of women. Similar observations were reported by others [2,8] . Casey et al [10] observed hypothyroid women to be older and U Nayki et al [14] .…”
Section: Discussionsupporting
confidence: 93%
“…Prevalence of hypothyroidism in our study is 38%. Prevalence reported by Deshpande S et al [8] is 17.5%. The prevalence of 2.2% is reported by others [9,10] .…”
Section: Discussionmentioning
confidence: 84%
“…10 Deshpande S et al, also found that there was a significant association between preeclampsia and thyroid hypofunction (p= .0406). 11 However, contrary to this, thyroid function changes were not found in preeclamptic patients in the study of Khadem M et al 12 In the present study, majority of the patients i.e 57.1% of the preeclamptic patients with thyroid dysfunction and 62.3% of euthyroid preeclampsia patients were in the age group of 26 to 35 years. Nulliparity accounted for 45.2% of the preeclamptic women with thyroid dysfunction and 45.3% of the euthyroid ones.…”
Section: Discussioncontrasting
confidence: 72%
“…10 Despande S et al, also reported that severe preeclampsia patients had 2.87 times more chances of thyroid hypofunction. 11 Wilson KL et al, reported that women with subclinical hypothyroidism in pregnancy have an increased risk of severe preeclampsia when compared with euthyroid women. 14 In contrast, Sheela SR et al, reported that changes in the thyroid hormones did not correlate with the severity of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…6 Deshpande et al carried out a study which shows significant association between preeclampsia and thyroid hypo function, with p value being 0.0406. 7 In our study 16 (4.2%) cases were associated with diabetes mellitus (Table 2) and 2 cases of overt diabetes mellitus patients had mild anemia. Ganesh et al in their study said that the likelihood of preeclampsia nearly increases by 8.7 (OR=8.7) times if diabetes is present before pregnancy.…”
Section: Discussionsupporting
confidence: 48%